THE EFFECT OF POLITICAL CONNECTION OF CSR DISCLOSURE WITH PROFITABILITY AS MODERATING VARIABLE - Erdayosi Erdayosi; wika Arsanti Putri (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2019)
The purpose of the study is to examine the effect of political connection to the level of voluntary corporate social responsibility disclosure with profitability as a moderating variable. Political connection in this research using 2 proxies that are the government share ownership and the board of directors. The sample of this study was 110 state-owned companies listed on the Indonesia Stock Exchange (IDX) for the period 2012-2017. The sampling method uses purposive sampling technique. The analytical tool used is simple linear regression analysis and analysis of Moderated Regression Analysis (MRA). The results of the study found that political connection of the government ownership and board director doesn’t show any significant effect toward CSR disclosure. Profitabilias, as a moderating variable, doesn’t moderate the influence of political connection using both proxies toward corporate social responsibility disclosure. The study makes a significant contribution to the literature by examine the influence political connection and CSR using neo-pluralist perspective of legitimacy theory. The implication of this research was suggested to increase the sector and more detail proxy of the research variable.